COVID-19 anxiety and quality of life among Iranian nurses - Zohreh Mohamadzadeh Tabrizi; Fatemeh Mohammadzadeh; Arezoo Davarinia Motlagh Quchan; Narjes Bahri (BMC, 2022)
Abstract Background The Coronavirus Disease 2019 (COVID-19) pandemic has exposed nurses, who are a very important group involved in the care of these patients, to many stresses that may affect their quality of life. This study aimed to determine the relationship between COVID-19 anxiety and the quality of life among Iranian nurses. Method This online cross-sectional study enrolled 1,131 of Iranian nurses working at the time of the COVID-19 outbreak in treatment centers in different parts of Iran from April to May 2020. The convenience sampling strategy was used. Data were collected using a demographic questionnaire, the 36-Item Short-Form Health Survey (SF-36), and Corona Disease Anxiety Scale (CDAS). The stepwise multiple linear regression models were used to examine the relationships among self-reported anxiety concerning COVID-19 and SF-36 quality of life, its components, and subscales. Partial r was used as an estimate of effect size. Result The mean SF-36 score was 65.2 (SD=17.6). The mean score of the mental component summary (MCS) (M=56.8, SD=22.3) was lower than the mean score of the physical component summary (PCS) (M=71.6, SD=17.5). The mean score of COVID-19 anxiety was 17.8 (SD=10.5). Of the participants, 378 (33.4%; 95% CI [30.7%, 36.3%]), and 152 (13.4%; 95% CI [11.5%, 15.6%]) reported moderate and severe anxiety, respectively. According to the results of stepwise multiple linear regression model, after adjusting for possible confounding variables, the SF-36 quality of life was still significantly negatively associated with COVID-19 anxiety, with a large effect size (The partial r = -0.515, p < 0.001). The relationship between the SF-36 components and COVID-19 anxiety were also significant, and moderate to large effect sizes were observed (The partial r for (PCS; COVID-19 anxiety) = -0.404; p < 0.001, and for (MCS; COVID-19 anxiety) = -0.521; p < 0.001). In addition, significant correlation coefficients for every subscale of the SF-36 were found for COVID-19 anxiety and its two components, with small to large effect sizes (The partial correlations= -0.211 to -0.524, all ps< 0.001). Conclusions The results showed that higher COVID-19 anxiety in nurses decreases their quality of life. In order to increase nurses' quality of life during the COVID-19 pandemic, it is recommended to design and implement programs to reduce their COVID-19 anxiety.